2002
DOI: 10.1016/s0735-1097(01)01737-5
|View full text |Cite
|
Sign up to set email alerts
|

High coronary artery calcium scores pose an extremely elevated risk for hard events

Abstract: A high CS (> or = 1,000) on a screening EBT in an asymptomatic person portends a very high risk of an HCE in the short term. This risk appears to be greater than the risk associated with a severe perfusion abnormality on MPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
148
0
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(162 citation statements)
references
References 43 publications
2
148
0
12
Order By: Relevance
“…Furthermore, we have demonstrated that concentric hypertrophy (wall thickness and concentricity) was associated with elevated CRP, although this association appears to be mediated via the risk factors for LVH rather than by LVH itself. Thus, patients with concentric LVH may be at increased risk for incident atherothrombotic events because of the synergistic combination of increased atherosclerotic burden [43][44][45][46][47] in the setting of coexisting risk factors associated with a proinflammatory milieu. 48 -51 Previous data have suggested that LVH may be associated with CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that concentric hypertrophy (wall thickness and concentricity) was associated with elevated CRP, although this association appears to be mediated via the risk factors for LVH rather than by LVH itself. Thus, patients with concentric LVH may be at increased risk for incident atherothrombotic events because of the synergistic combination of increased atherosclerotic burden [43][44][45][46][47] in the setting of coexisting risk factors associated with a proinflammatory milieu. 48 -51 Previous data have suggested that LVH may be associated with CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Whether coronary calcium is independent and superior to conventional risk factors as a predictor for future cardiac events is not yet well established. 11 Future randomized large prospective studies (eg, Prospective Army Coronary Calcium study 12 ) may provide the definitive evidence of the predictive value of CS.…”
Section: Ebct For Coronary Calciummentioning
confidence: 99%
“…Detection and quantification of arterial calcification now can be easily achieved by the use of newer imaging techniques such as electron-beam computed tomography (EBCT) and multislice computed tomography (2,3). In the general population, coronary artery calcium (CAC) score as measured by EBCT was found to be an independent predictor of subsequent cardiac events in both symptomatic and asymptomatic individuals (3,4).…”
mentioning
confidence: 99%